"Common factors", cointegration, and Japan's aggregate import demand function - Tang, Tuck Cheong (Universita Putra Malaysia, 2015)
This study surveys the existing studies those examined a long-run (cointegration) aggregate import demand for Japan. Their empirical results are inconclusive on the "cointegratedness" of Japan's aggregate demand for imports, and its determinants, namely activity variable, and relative price of imports. A set of determinants or socalled "common factors" is identified from the literature, and the empirical results provide some meaningful findings. An implication of this study is that the "common factors" have to consider when carrying out cointegration analysis, in particular, for the aggregate import demand function.